Design, Synthesis, Docking-Based Virtual Screening and Anticonvulsant Evaluation of Novel Isatin-linked Benzothiazole Hybrids - Dubey, Bhavana; Singh, Kuldeep; Kumar, Arun; Hasan, Syed Misbahul; Suvaiv; Kushwaha, Shom Prakash; Kumar, Praveen (Asian Journal of Chemistry, 2026)
Benzothiazole and isatin scaffolds possess considerable biological importance and their molecular hybridization may provide a promising approach for enhancing anticonvulsant activity. The present study focused on the design, synthesis and evaluation of a novel series of 6-substituted-N'-(5-substituted-2-oxoindolin-3-ylidene)benzo[d]thiazole-2-carbohydrazide derivatives (IBS01-IBS08) using computational and experimental approaches. Molecular docking studies were performed using AutoDock 1.5.6 against γ-aminobutyric acid (GABA) aminotransferase (PDB ID: 1OHV) to investigate the binding interactions of the synthesized derivatives. The compounds were synthesized and characterized by IR, NMR and mass spectrometry. Their anticonvulsant activity was evaluated in vivo using the maximum electroshock seizure (MES) model at doses of 30 and 100 mg/kg, with hind-limb tonic extension (HLTE) used as the primary endpoint. Phenytoin (25 mg/kg, i.p.) served as the reference standard. The rotarod test was employed to assess motor coordination deficits. The docking results shows the valuable binding interactions of the synthesized hybrids with GABA-aminotransferase. All derivatives markedly decreased the duration of MES-induced HLTE without causing death. Phenytoin demonstrated significant anticonvulsant efficacy (***p < 0.0001) throughout all convulsive phases. The Rotarod test revealed no significant neurotoxic effects at the tested active doses. The synthesized benzothiazole-isatin hybrids exhibited significant anticonvulsant activity, favourable in silico binding affinity and low neurotoxicity, supporting their potential as lead structures for further development of antiepileptic agents.